Comparison of contrast‐enhanced ultrasonograpy with Gd‐EOB‐DTPA‐enhanced MRI in the diagnosis of liver metastasis from colorectal cancer. Issue 3 (12th November 2016) - Shiozawa, Kazue; Watanabe, Manabu; Ikehara, Takashi; Matsukiyo, Yasushi; Kogame, Michio; Kikuchi, Yoshinori; Otsuka, Yuichiro; Kaneko, Hironori; Igarashi, Yoshinori; Sumino, Yasukiyo
ABSTRACT: Purpose: To compare contrast‐enhanced ultrasonography (CEUS) using Sonazoid with Gd‐EOB‐DTPA‐enhanced MRI (EOB‐MRI) in the diagnosis of liver metastases in patients with colorectal cancer. Methods: A total of 69 patients diagnosed with or suspected of having liver metastasis were enrolled. These hepatic lesions were diagnosed by histopathological examination after surgical resection or based on follow‐up using various imaging modalities. The diagnostic accuracies of CEUS and EOB‐MRI were compared. Results: One hundred thirty‐three lesions were detected. Of these lesions, 109 were diagnosed as liver metastases. Of the 133 lesions, 90.2% were detected on CEUS, and 98.5% on EOB‐MRI. One hundred nine lesions were diagnosed as liver metastasis. The areas under the receiver operating characteristic curve for diagnosis were 0.906 and 0.851 on CEUS and EOB‐MRI, respectively ( p = 0.41). Sensitivity, specificity, positive predictive value (PPV), negative predictive value, and overall accuracy were 90.8%, 84.5%, 97.1%, 67.1%, and 90.2%, respectively, for CEUS, and 95.4%, 70.8%, 93.7%, 77.3%, and 91%, respectively, for EOB‐MRI. Conclusions: CEUS has a higher specificity and PPV for the diagnosis of liver metastasis than EOB‐MRI. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :138–144, 2017